Design of Online Certificate Data Processing Information System in Metrology Jakarta - Angga Prasetya; Eva Zuraidah (Jurnal Mantik, 2020)
In the current era of globalization in the Jakarta Metrology Management Unit Services, currently completing work is still manual, both receipt of goods, recording/registration, to the archiving that has an important role in an office, if the records are poorly managed, it can be difficult to find data that has been stored and finally can hamper the next stage of the work process. Therefore the Jakarta Metrology Management Unit needs an application or a way to complete the work efficiently and effectively so that data processing work can be done quickly and accurately. This web-based information system can also facilitate registrants in checking data, so the authors in designing this information system using the sublime text application and by using the waterfall method, in designing this information system are modeled by Unified Modeling Language (UML). Using the Hypertext Prepocessing (PHP) programming language with Mysql as a database. The final result of this study is so that companies can more easily process data. Online Certificate Data Processing Information System based on the web, on this website the registrant can see directly their data process so that after completing the certificate.